Dilema Dispensasi Kawin Pasca Dinaikkanya Batasan Usia Perkawinan - Dyah Auliah Rachma Ruslan (PAMALI: Pattimura Magister Law Review, 2022)
Introduction: The regulations governing marriage in Indonesia have determined the minimum age for a person to enter into a marriage. The increase in the age limit for marriage resulted in an increase in the number of requests for dispensation for marriage in court and almost all of them were granted by the court. This certainly hampered the government's efforts to reduce the number of underage marriages which are seen as having many negative impacts.Purposes of the Research:  To see the effectiveness of the regulation regarding the age limit for entering into marriage which was raised to 19 (nineteen) for men and women which is associated with the high demand for dispensation from marriage in court..Methods of the Research: The research method used is normative legal research. The main subject of the study is law which is conceptualized as a norm or rule that applies in society and becomes a reference for everyone's behavior.Results of the Research: The rules governing the age limit for marriage, which is 19 (nineteen) years for men and women, are still not effective. This can be seen by the many requests for dispensation from marriage that have been filed in court and almost all of them have been granted. There are still many people who do not understand the negative impacts of underage marriages, which means that there are still many requests for dispensation from marriage. Courts should be able to pay attention in more detail and selectively regarding the aspects that are considered in granting approval for marriage dispensation